Drying Peppers: Technolocy and Properties - Guiné, Raquel (2016)
The peppers can be very diverse, from sweet to hot peppers, varying in shape, in colour, in properties and usages. While some are eaten in the fresh state, many of them undergo a drying process to be preserved for a longer time and to increase availability and convenience. Hence, after harvesting, in many cases a drying operation is involved, and the present chapter aims to address this operation, of pivotal importance. In ancient times, the drying of foods in general and peppers in particular was done by exposure to the solar radiation. However, despite its cheapness and easiness, this process involved many drawbacks, like long drying times, probability of adverse atmospheric conditions and contaminations of the product. Hence, nowadays its usage is reduced. The most popular industrial drying method is the hot air convective drying. However, the high temperatures to which the product is exposed can cause changes in the composition and nutritional value as well as in the physical properties or organoleptic quality of the products. Other alternative methods can be used, but sometimes they are more expensive or more time consuming, such as is the case of freeze drying. Still, this last also has visible advantages from the quality point of view, minimizing the changes in texture, colour, flavour or nutrients. The knowledge of adequate drying operating conditions allows the optimization of the product characteristics, and hence to know the drying kinetics or the isotherms is fundamental to properly design the most adequate drying processes, and therefore preserve the organoleptic characteristics as well as the bioactive compounds present.